Upaya meningkatkan hasil belajar passing pada permainan sepakbola melalui pendekatan bermain kreatif pada siswa SMP di Makassar - Benny B (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to determine the increase in the results of passing football learning through a learning model approach to creative play for students of Makassar Public Middle School 24. The method in this study uses Class Action Research approach. The instrument used in this study is a portfolio sheet. The subjects in this study were eighth grade students of Makassar Middle School 24, which numbered 30 people. Based on the results of the research in the form of initial activities, follow-up activities (cycle I) and cycle II through a model of creative play approach, it was found that the ability to improve passing learning results in playing football significantly. The average percentage value of students in Cycle I was 11 students or 36.67% (complete) and 19 students or 63.33% (incomplete), and in the implementation of Cycle II there were 29 students or 96.67% ( complete) and 1 student or 3.33% (incomplete). Learning outcomes have increased from 68.8 to 82. So it can be concluded that there is an increase in the results of learning passing on football games to students of Makassar 24 Public Middle School through creative learning.